The Influence of COVID-19 Lockdown on Physical Activity, Sedentary Behavior and Social Support Specific to Physical Activity Among Belgian Adults - Pierre Van Luchene; Fanny Detemmerman; Cécile Delens (Frontiers Media S.A., 2021)
In Belgium, lockdown measures were taken to counter the spread of COVID-19. This major life-change event may disrupt a person's daily routine and influence health behaviors. Although measures were restrictive, citizens were encouraged to engage in physical activity (PA) behavior in order to maintain well-being. Social support specific to PA (SSPA) had been highlighted as an important psychosocial factor in initiating and/or maintaining active behavior. The main aims of this study were to explore the influence of COVID-19 lockdown on PA and sedentary behavior, and on SSPA from family and from friends; and investigate the potential differences in terms of professional status. An online survey was distributed during the 1st weeks of the lockdown. A total of 272 Belgian adults responded to the survey. The findings show no significant difference between prior to and during lockdown with regard to the amount of PA. The results show a significant increase in sedentary behavior among the entire sample, workers and retirees. The findings also suggest that the support of other individuals is particularly useful for certain population groups such as retirees. Given the importance of the levels of PA and sedentariness as health behaviors preceding a major life-change event such as a lockdown, there is a need to promote these health behaviors during normal life in order for the population to remain active throughout their lifespan.